Seed tolerance to post-fire temperature fluctuation of Cerrado legume shrubs with micromorphological implications - Daibes, L. Felipe [UNESP]; Martins, Aline R. [UNESP]; Silveira, Fernando A.O.; Fidelis, Alessandra [UNESP] (Elsevier, 2021)
Multiple environmental cues may break seed physical dormancy (PY) in fire-prone ecosystems, but disentangling the roles of such cues remains challenging. Current research has mostly focused on the role of high temperatures (heat shocks) in PY alleviation, while post-fire environmental conditions are less understood. Here, we examined the role of post-fire temperature fluctuation on seed germination and viability of Cerrado legume shrubs. Specifically, we investigated (1) whether PY is broken by temperature fluctuation; (2) whether seed viability is affected by temperature fluctuations; and (3) micromorphological changes in the seed coat following exposure to temperature fluctuation. Seeds of nine legume species were collected in frequently burned Cerrado savannas. We simulated post-fire temperature fluctuation in germination chambers, with daily temperature fluctuation ranging from 18 to 55 °C for 90 days; controls consisted of untreated seeds (room temperature). We conducted germination trials with unblocked and blocked hilar region of seeds. In addition, seed samples were fixed and subjected to micromorphological analysis. Instead of dormancy break, three species showed decreased seed germination for both unblocked and blocked hilar regions, while other two species showed decreased germination in blocked seeds only. Nevertheless, random cracks formed across the seed coat were found in control and treated seeds, which displayed a proportion of nondormant seeds. Within nondormant seeds, both hilar and extra-hilar regions (such as the pleurogram) may take part on water uptake. Despite the lack of dormancy break, most Cerrado legume seeds persisted viable after post-fire temperature fluctuation, thus avoiding establishment under hazardous conditions. Seed tolerance to heat shocks and post-fire temperature fluctuation likely drives regeneration from seed in burned Cerrado areas.
Keywords: Brazilian savannas; Germination; Leguminosae; Physical dormancy; Soil heat